Information search trends about sharia: a comparation study between business-industry genre with book-literature genre - Akhmad Kusuma Wardhana (Universitas Airlangga, 2020)
Indonesia has a large sharia market potential. This is because Indonesia has the largest Muslim population in the world. The market potential is supported by the openness of information via the internet. This study aims to observe trends in information search on the internet about sharia with comparative studies on the genre of